A Primary Hepatic Lymphoma Treated with Liver Resection and Chemotherapy. (4th August 2014) - Bouliaris, Konstantinos; Christodoulidis, Grigorios; Koukoulis, Georgios; Mamaloudis, Ioannis; Ioannou, Maria; Bouronikou, Eleni; Palassopoulou, Maria; Tepetes, Konstantinos
Abstract : Primary hepatic lymphoma (PHL) is a rare malignancy, which is frequently misdiagnosed. Although chemotherapy is the treatment of choice there are reports that a combination of surgery and adjuvant chemotherapy can offer better results. Herein we present an interesting case of a large primary non-Hodgkin lymphoma originating from liver was treated with a liver which resection and chemotherapy.